Pattern of skin diseases and occupational dermatoses among paddy field workers in kashmir valley: A cross-sectional study from North India - Shahnawaz Bashir; Iffat Hassan; R T Wani; Sumaya Zeerak; F Y Shah (Wolters Kluwer Medknow Publications, 2021)
Introduction: Paddy farming is one of the main occupations in Kashmir valley. The workers associated with paddy are exposed to variety of irritants such as manures, fertilizers, and pesticides, besides getting exposed to intense sunlight for long hours due to the nature of their work. All these factors can potentially either trigger skin diseases or can worsen them. Aim: The aim of this study was to find out the prevalence and pattern of various skin disorders among paddy field workers in Kashmir valley. Materials and Methods: This was a cross-sectional descriptive study in which 600 workers engaged in paddy farming in different areas of Kashmir valley were screened. The diagnosis was made on clinical grounds and wherever deemed necessary, relevant investigations were carried out to establish the nature of the disease. Results: A total of 600 workers were evaluated for the presence of skin disorders. Two hundred thirty workers (38.3%) were found to have skin lesions, while the rest, i.e. 370 (61.7%) were free from any skin problem. Out of the total skin lesions, infectious ones were seen in 40.4%, while non-infectious accounted for 59.6% cases. The main non-infectious disorders included melasma, followed by hand and foot eczemas, hyperkeratosis of palms and soles and callosities/cuts, while among the infectious group the major chunk was formed by bacterial infections followed by fungal, viral, and parasitic. Pitted keratolysis and intertrigo were the most common bacterial and fungal infections respectively. Conclusion: A large number of skin diseases were seen in paddy field workers, with some diseases showing an occupational nature.